국내 고령자의 Y-DuCog 표준치, 인지기능에 관한 연구 - 곽호성; Kwak, Hosoung (Journal of the Korean Society of Integrative Medicine, 2020)
Purpose : This study aimed to present normative data for older Korean adults completing the Yonsei dual task cognitive screening test (Y-DuCog) and identify changes in cognitive function on the Montreal Cognitive Assessment - Korean (MoCA-K) with age. Methods : From May 2019 to August 2019, 195 healthy adults aged ≥60 years participated in this study. All participants completed the Y-DuCog to assess their dual-task performance and the MoCA-K to assess their cognitive function. Participants were divided into three groups based on their age: 60~69 years, 70~79 years, and ≥80 years. Results : The results of the Y-DuCog showed that dual-task performance time, effect, and correct response rate decreased significantly with age (p<.001). Scores from the three groups showed differences on all items (p<.001). Cognitive function on the MoCA-K also decreased significantly with age (mean score ± standard deviation [SD]; 27.33 ± 2.61 in subjects aged 60~69 years; 24.82 ± 3.20 in subjects aged 70~79 years; and 22.10 ± 4.91 in subjects aged ≥80 years; p<.001). Conclusions : Occupational therapists should be aware of the decline in cognitive function and dual-task performance time, effect, and correct response rate in older adults and consider interventions to treat this decline. Further studies are needed with larger groups of participants to examine factors, such as sex and education, that may impact dual-task performance and cognitive function.